(untitled) (Jurnal Sejarah Indonesia, 2024)
This paper aims to explain the natural disaster of drought which influenced the decline in the economy and high crime in Lamongan. This paper uses historical research methods which include the stages of topic selection, heuristics, verification, interpretation, and historiography by paying attention to the focus of the study on urban issues, especially environmental and social history. Based on research results, it is known that the drought in Lamongan was caused by climate anomalies and erratic climate change. This drought has had various impacts, ranging from a lack of water supply for agriculture, scarcity of food to the rise of crime such as theft. The efforts to overcome drought were carried out by the colonial government with the cooperation of local residents, such as carrying out repairs to reservoirs, holding prayer events, and joint celebrations to ask God for help. Even though this drought disaster cannot be avoided, its impact can be minimized with mitigation efforts.